Online News Portals and Journalistic Code of Ethic (The study of news independence value on Viva.co.id and Republika.com regarding the fuel price rising in 2022) - Pratama, Khabib Fajar; Puspitasari, Fingky Ayu (Universitas Muhammadiyah Ponorogo, 2023)
This research is motivated by the emergence of online news portals that becomes one of the efforts made by the conventional media in order toper form media convergence. Media inthenet work or online media becomes the most popular news source for Indonesian people today. Unfortunately, online media journalists are not considered as professional as print media journalists.This conditionis inseparable from the several violation sof journalistic rules inthenet work or internet as well as the journalistic code of ethics committed by the online media journalists. This study analyzes the content of the news posted on two online news portals, Viva.co.id and Republika.com. There search problemis focused on how independent the appearance of the news related to the issue of fuel price risingin 2022. For the techniques of analysis, this study applied Miles and Huberman’scontent analysis model and data interpretation associated with the Journalistic Code of Ethics. The results showed that the news posted on Viva.co.id and Republika.com regarding the fuel price rising in 2022 appeared with an independent face.However,the published new sun fulfilled the elements of news and a good journalistic code of ethics. In thiscase, there were not found the elements of 5W (What, Why, Who, When, Where) and 1 H (How) in the news. Moreover, it still included the author's opinion. In addition, there was also a discrepancy between the title of the news and the content of the news. The results of the analysis pointed out the presence of sensationalism (emotionalism and dramatization) in the news content. The news posted on Viva.co.id contain the elements of personalization toward the negative impact of fuel price rising, thus reader sareledto negative opinion sand stereotypes to the related object. Whereas, the news posted on Republika.com contain the elements of personalization toward the government.Thus, the readers are presented with positive opinion sand stereotypes to particular object.